Curadoria museológica: o acervo de espadas do Museu do Instituto Histórico e Geográfico do Pará - BESSA, Adriele Vitória do Nascimento (2019)
This paper is a case study of the curator of the collection of swords Museum of Pará Historical and Geographical Institute (IHGP) that has been developed through volunteer Project of Identification and Museological Collection of Documentation of MIHGP, and aims to present the importance documentation and museological research through the curatorial action in collections, discussing the importance of these methods to the safe-guarding of museum collections. For this survey was developed as a methodology and qualification of the collection, typological research and the methods of documentation and conservation. With these methods we proposed a procedure for storing the swords and a cataloging record designed for the entire collection of Museum, showing how these curatorial actions contribute to better management of the museum's collections.